Cyclosporin A increases recovery after spinal cord injury but does not improve myelination by oligodendrocyte progenitor cell transplantation - Lü, He-Zuo (BioMed Central, 2010)
BACKGROUND: Transplantation of oligodendrocyte precursor cells (OPCs) is an attractive therapy for demyelinating diseases. Cyclosporin A (CsA) is one of the foremost immunosuppressive agents and has widespread use in tissue and cell transplantation. However, whether CsA affects survival and differentiation of engrafted OPCs in vivo is unknown. In this study, the effect of CsA on morphological, functional and immunological aspects, as well as survival and differentiation of engrafted OPCs in injured spinal cord was explored. RESULTS: We transplanted green fluorescent protein (GFP) expressed OPCs (GFP-OPCs) into injured spinal cords of rats treated with or without CsA (10 mg/kg). Two weeks after cell transplantation, more GFP-positive cells were found in CsA-treated rats than that in vehicle-treated ones. However, the engrafted cells mostly differentiated into astrocytes, but not oligodendrocytes in both groups. In the CsA-treated group, a significant decrease in spinal cord lesion volume along with increase in spared myelin and neurons were found compared to the control group. Such histological improvement correlated well with an increase in behavioral recovery. Further study suggested that CsA treatment could inhibit infiltration of T cells and activation of resident microglia and/or macrophages derived from infiltrating monocytes in injured spinal cords, which contributes to the survival of engrafted OPCs and repair of spinal cord injury (SCI). CONCLUSIONS: These results collectively indicate that CsA can promote the survival of engrafted OPCs in injured spinal cords, but has no effect on their differentiation. The engrafted cells mostly differentiated into astrocytes, but not oligodendrocytes. The beneficial effect of CsA on SCI and the survival of engrafted cells may be attributed to its neuroprotective effect.